Infectious Salmon Anemia Virus Shedding from Infected Atlantic Salmon (Salmo salar L.)—Application of a Droplet Digital PCR Assay for Virus Quantification in Seawater - Weli, Simon Chioma; Bernhardt, Lisa-Victoria; Qviller, Lars; Dale, Ole Bendik; Lillehaug, Atle (Viruses, 2021)
Infectious salmon anemia virus (ISAV) infection is currently detected by fish sampling for PCR and immunohistochemistry analysis. As an alternative to sampling fish, we evaluated two different membrane filters in combination with four buffers for elution, concentration, and detection of ISAV in seawater, during a bath challenge of Atlantic salmon (Salmo salar L.) post-smolts with high and low concentrations of ISAV. Transmission of ISAV in the bath challenge was confirmed by a high mortality, clinical signs associated with ISA disease, and detection of ISAV RNA in organ tissues and seawater samples. The electronegatively charged filter, combined with lysis buffer, gave significantly higher ISAV RNA detection by droplet digital PCR from seawater (5.6 × 104 ISAV RNA copies/L; p < 0.001). Viral shedding in seawater was first detected at two days post-challenge and peaked on day 11 post-challenge, one day before mortalities started in fish challenged with high dose ISAV, demonstrating that a large viral shedding event occurs before death. These data provide important information for ISAV shedding that is relevant for the development of improved surveillance tools based on water samples, transmission models, and management of ISA.